Constructing and exploring the model to form the road map of enterprise development - Onyshсhenko Svitlana; Bondar, Alla; Andrievska, Vera; Sudnyk, Nadiia; Lohinov, Oleh (Eastern-European Journal of Enterprise Technologies, 2019)
The study addresses the task on determining the optimal road map for the enterprise development – the choice of the sequence of projects and their parameters, which would ensure the achievement of the goal taking into consideration the basic requirements and constraints. The optimization of the structure and parameters of the development road map is carried out based on the "strategic network" that makes it possible to form alternative variants of the road map of development. This network is based on the principle of the formation of transport networks, and the space "time – indicators of the enterprise state" is accepted as the analogue of the topological space. The elements of the strategic network – "nodes" – are the enterprise states and the projects that correspond to network transitions from one state to another. The network parameters include: duration of transition from state to state, determined by the intensity of project activities; duration of the project funding process; beginning of the project implementation (transition to a new stage). These parameters determine the following characteristics of the projects that form the characteristics of the road map: project costs; root mean square deviation of project costs; financial result after the project implementation; root mean square deviation of the financial result after the project implementation. The model for establishing the optimal structure and parameters of the road map of the enterprise development was developed. This model makes it possible to determine the optimal road map of the enterprise development, taking into consideration the possibility of varying the time parameters: time of beginning of each stage, duration of transition from stage to stage, duration of funding phases. The model takes into consideration the probabilistic nature of investment costs and inflows of the funds of an enterprise after the implementation of development activities. Experimental studies on the formation of a road map based on the developed model were carried out, which proved its operation capacity and reliability. The model can find a wide practical application in solving the issues on the construction of road maps of a step-by-step increase in production, or a phased replacement of equipment (technical development)